Modus Operandi Dan Penegakan Hukum Tindak Pidana Pembalakan Liar Di Kawasan PBPH PT. Kirana Chatulistiwa - Sitasari Rizqi Mahanani; Syarif Nurhidayat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Criminal acts committed by perpetrators of Illegal Logging caused losses for PT. Kirana Chatulistiwa in the form of damage to forest areas. Logging that should have been done legally was illegally logged by a corporation to open plantation land illegally. This raises questions about the modus operandi of Illegal Logging carried out by the perpetrators and how the law enforcement of Illegal Logging in the PBPH area of ​​PT. Kirana Chatulistiwa. The author conducts research using empirical methods that focus on a person's behavior which is obtained by the interview method and through a sociological juridical approach by looking at legal facts or legal realities in society. The results of this study are that the perpetrators carried out their modus operandi by claiming to be indigenous people in the local area so they could cut down trees and take advantage of PT. Kirana Chatulistiwa which at that time was being abandoned. Furthermore, the legal settlement was carried out by the KPH Kusan team and the company by sending subpoenas, giving direct warnings, and compensation made by PT. Kirana Chatulistiwa and the application of the social forestry system between PT. Kirana Chatulistiwa with the perpetrators.